Influence of nanometric microstructural development on thermophysical properties of lanthanum-doped strontium titanate - Idza Riati, Ibrahim; Khamirul Amin, Matori; Ismayadi, Ismail; Siti Nor Ain, Rusly; Rodziah, Nazlan; Nor Hidayat, Yusof; Mohd Hafiz, Mohd Zaid; Chanlek, Narong; Nakajima, Hideki; Norni Hidayawati, Mat Daud; Bahmanrokh, Ghazaleh (Elsevier, 2021)
The evolution of imperfect crystal from a highly amorphous structure to an ordered crystalline structure via sintering has demonstrated a significant development onto the thermophysical properties. Therefore, a series of La-doped strontium titanate with different morphological properties have been synthesized via high energy ball milling with subsequent sintering. Doping of lanthanum tends to inhibit the grain growth where a significant reduction of grain size (range from 34 nm to 0.47 μm) could be observed. A large amount of grain boundaries presence with fine grains, resulting from lanthanum doping, has enhanced phonon scattering, thus yielding a low heat propagation in La-doped SrTiO3. Besides acting as a grain growth inhibitor, lanthanum also acts as a scattering centre due to imperfection created by the doping. The scattering mechanisms significantly decrease the phonon mean free path. Consequently, the thermal diffusivity has been efficiently reduced to 1.1 mm2/s as compared to that of pure SrTiO3 which showed a value of about 3.8 mm2/s, both observed for the complete phase polycrystalline materials. The systematic development of thermophysical and morphological properties of La-doped SrTiO3 can be served as a preliminary guide to engineer thermoelectric materials with low thermal diffusivity.